P1133XYLITOL-BASED PERITONEAL DIALYSIS SOLUTIONS MITIGATED IN VITRO MESOTHELIAL AND ENDOTHELIAL TO MESENCHYMAL TRANSITION. (6th June 2020) - Masola, Valentina; Arduini, Arduino; Bonomini, Mario; Gambaro, Giovanni; Zaza, Gianluigi
Abstract: Background and Aims: Fibrosis, angiogenesis and microvascular alteration are main pathogenetic mechanisms involved in the progressive loss of the peritoneal ultrafiltration capacity in patients undergoing peritoneal dialysis (PD). Main cause of this condition is the continuous peritoneal exposure to hyperosmotic and hyperglycaemic agents. High glucose level activates the Mesothelial to Mesenchymal Transition (MMT) and the Endothelial-to-Mesenchymal (EndMT) program, which are responsible for the development of fibrosis/chronic peritoneal damage. Moreover, the high glucose content of PD solution may induce the VEGF production with consequent neo-angiogenesis. Therefore, the introduction of more biocompatible solutions in clinical practice is necessary for preserving the long-term peritoneal membrane. To this purpose we tested the in vitro effects of a new commercially available PD solutions containing xylitol, carnitine and reduced glucose, at comparable osmotic strength (XyloCore). Method: Human vein microvascular endothelial cells (HMVEC) were cultured in EGM™-2MV medium (Lonza) and Human peritoneal mesothelial cell line (HMrSV5) were cultured in Dulbecco's Modified Eagle Medium (DMEM; Gibco) containing 10% fetal bovine serum. Cells were cultured to confluence and then treated for 3 hours with serum free medium, XyloCore 0.7 (0.5% Glucose, 0.7% Xylitol and 0.02% L-carnitine), XyloCore 1.5 (0.5% Glucose, 1.5% Xylitol and 0.02% L-carnitine) and commercially available glucose-based solutions (Fixioneal) 1.36% and 2.27% Glucose. Gene expression of MMT/EndMT, apoptosis, inflammation, extracellular remodeling and angiogenesis markers was evaluated by real-time PCR. Cell viability was assayed by MTS assay. Results: Our in vitro results demonstrated that XyloCore solutions, by influencing only partially the mesothelial and endothelial cells viability, demonstrated a good biocompatible profile. Then, gene expression analysis of HMVEC and HMrSV5 treated with XyloCore solutions revealed a significant down-regulation of transcripts encoding for MMT and EndMT biomarkers (Zinc finger protein SNAI1, TGF-beta, alpha-SMA and vimentin), and pivotal biological elements involved in apoptosis (Bcl-2), extracellular matrix remodeling (matrix metallopeptidases), inflammation (IL-1beta, IL-6) and angiogenesis (Vascular endothelial growth factor) compared to glucose-based solutions with comparable osmotic strength. Conclusion: These in vitro results demonstrated, for the first time, that XyloCore solutions have a better biocompatible impact and less pro-fibrotic potentials compared to conventional glucose-based solutions. These effects, if confirmed in in vivo studies, could have interesting clinical potentials.